Procesamiento de la yuca para pequenos productores: Adaptacion y mejoramiento de una maquina picadora de yuca para el uso de cooperativas de agricultores - Best, R.; Alonso, L.; León G, A. (International Center for Tropical Agriculture, 1986)
Research work carried out at the commercial plant level and at the exptl. level to improve the design and utility of the Thai-type cassava chipper is described. The evaluation of 3 other types of cassava chipper (Malaysian, Colombian, and Brazilian) is presented; they are compared in terms of their mechanical performance and the drying characteristics of the chips produced. It is concluded that the Thai-type cassava chipper can be used in the natural cassava drying plants of the Colombian Atlantic Coast. The Malaysian- and Brazilian-type chippers did not offer advantages as to greater capacity, lower costs, or greater dehydration efficiency. The Colombian-type blade can be easily adapted to the existing chippers; the drying efficiency would be improved due to the more uniform chips. (CIAT)